HUBUNGAN DUKUNGAN KELUARGA DENGAN KEPATUHAN DIET RENDAH PURIN PADA PENDERITA GOUT ARTHRITIS DI UPT PUSKESMAS HELVETIA MEDAN: HUBUNGAN DUKUNGAN KELUARGA DENGAN KEPATUHAN DIET RENDAH PURIN PADA PENDERITA GOUT ARTHRITIS DI UPT PUSKESMAS HELVETIA MEDAN - Ilham Syahputra Siregar; Irma Handayani; Farah Dhiba; Nadia Nasmi (LPPM Universitas Abdurrab, 2025)
Abstract Gout Arthritis is a joint disease caused by high levels of uric acid in the blood exceeding normal limits, causing accumulation in the joints and other organs of the body, this accumulation makes the joints sore, painful, and inflamed. Gout arthritis sufferers control joint damage with non-pharmacological therapy including patient education, diet management, and aiming to reduce foods rich in purine as a natural gout control. Dietary compliance related to the treatment given, reducing the intake of foods high in purine helps control the production of uric acid in the body. Cases of gout arthritis need great support from the family related to nutrition, psychological conditions. Family support is an important factor in realizing compliance with medical programs. The purpose of this study was to analyze family support with low-purine diet compliance in Gout Arthritis sufferers in the Helvetia Medan Health Center work area in 2024. The research design was descriptive correlation with a cross-sectional approach. Purposive sampling technique, the sample of this study amounted to 48 respondents, the research instrument used a family support questionnaire sheet with low-purine diet compliance. Statistical tests using the Spearman Rho test. The results of the study showed that there was a relationship between family support and compliance with a low purine diet in gout arthritis patients at the Helvetia Health Center, Medan.